A novel visual short‐term memory task differentiates MCI and Alzheimer's patients from healthy ageing: Neuropsychology/computerized neuropsychological assessment. (7th December 2020) - Toniolo, Sofia; Maio, Maria R.; Tabi, Younes Adam; Slavkova, Elitsa; Plant, Olivia; Saleh, Youssuf; Attaallah, Bahaaeddin; Idris, Imran; Peixoto, Joao; Preul, Christoph; Srowig, Annie; Joedecke, Steffen; et al.
Abstract: Background: We developed a novel delayed reproduction task, the "What was where?" task, which obtains a continuous measure of localization error and is more sensitive compared to conventional span measures of Short‐term Memory (STM). Method: We recruited 44 MCI (Mild Cognitive Impairment), 41 AD (Alzheimer's Disease) patients and 109 healthy elderly controls (EHCs) from memory clinics in Oxford, UK and Jena, Germany, where they performed the "What was where?" task (Figure 1). We extracted the following metrics: Identification Accuracy (percentage correctly identified items), Absolute Localization Error (how far the object was misplaced), Misbinding rate (erroneously localizing an item to the remembered location of another item in memory) and Guessing response rate. Result: Absolute Localization Error and Misbinding rates were greater in MCI and AD patients (p < 0.001) compared to EHCs, while AD and MCI performed similarly on these metrics. However, Identification Accuracy as well as Guessing (p = 0.003) were greater in MCI (p < 0.001) compared to AD patients. Moreover, EHCs identified the correct object more often (p < 0.001) and guessed less (p < 0.001) than MCI patients. Conclusion: This novel task is able to detect STM impairment in MCI cases on a continuous scale, and is a sensitive memory measure which might be a useful index of memory for future clinical trials in AD in its earliest stages.